Iterative Optimal Control for Flexible Rotor–AMB System - G. Serdar Tombul; Stephen P. Banks; Nizami Akturk (Acta Montanistica Slovaca, 2010)
In this paper we propose an optimal control design technique for a class of nonlinear and control non-affine equations.The dynamic equations of a flexible shaft supported by a pair of active magnetic bearings (AMBs) are used as the nonlinear control nonaffineequations. The basic model of the system will be a Timoshenko beam supported at the ends by magnetic frictionless bearings.The effective control of such systems is extremely important for very high angular velocity shafts which are a feature of many modernmachines. The control must be able to cope with unbalanced masses and hence be very robust.In this paper we shall approach the problem by discretising the Timoshenko beam model and using standard difference formulaeto develop a finite-dimensional model of the system. Then we use a recently developed technique for controlling nonlinear systemsby reducing the problem to a sequence of linear time-varying (LTV) systems. An optimal control designed for each approximating linear,time-varying system and recent results show that this method will converge uniformly on compact time intervals to the optimal solution.